Multifunctional Poly(D,L-Lactide-co-Glycolide)/ Montmorillonite (PLGA/MMT) Nanoparticles Decorated by Trastuzumab for Targeted Chemotherapy of Breast Cancer - Ranganathan, Balu; Sun, Bingfeng; Feng, Si-Shen (Pan Stanford Publishing Pte. Ltd., 2014)
The book provides the necessary knowledge for scientists, engineers, and master’s and PhD students who want to be well prepared to work in the fields of chemotherapeutic engineering, cancer nanotechnology, and nanomedicine, or more generally in biomedical engineering. It also provides the basic knowledge and models for people who work in cancer clinics as well as in the pharmaceutical industry